2022
DOI: 10.3390/rs14081865
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Stratified and Multi-Stage Approach for National Land Cover Mapping Based on Sentinel-2 Data and Expert Knowledge

Abstract: Portugal is building a land cover monitoring system to deliver land cover products annually for its mainland territory. This paper presents the methodology developed to produce a prototype relative to 2018 as the first land cover map of the future annual map series (COSsim). A total of thirteen land cover classes are represented, including the most important tree species in Portugal. The mapping approach developed includes two levels of spatial stratification based on landscape dynamics. Strata are analysed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Sentinel-2 includes three red-edged vegetation and the SWIR bands that are highly susceptible to chlorophyll content and amend distinguishing different vegetation types and LCLU classification accuracy (Chaves et al 2020). Several studies found Sentinel-2 data with high potential in different applications such as crop classification (Hernandez et al 2020), tree species classification (Costa et al 2022, Wessel et al 2018, Persson et al 2018, mapping burned area (Pacheco et al 2021), and forest type classification (Kaplan 2021). Most of the recent studies have shown that non-parametric machine learning approaches such as Artificial Neural Network (ANN), Support Vector Machine (SVM), and Random Forest (RF) have a great potential to classify heterogeneous land covers (Wessel et al 2018, Pacheco et al 2021, Sheykhmousa et al 2020.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sentinel-2 includes three red-edged vegetation and the SWIR bands that are highly susceptible to chlorophyll content and amend distinguishing different vegetation types and LCLU classification accuracy (Chaves et al 2020). Several studies found Sentinel-2 data with high potential in different applications such as crop classification (Hernandez et al 2020), tree species classification (Costa et al 2022, Wessel et al 2018, Persson et al 2018, mapping burned area (Pacheco et al 2021), and forest type classification (Kaplan 2021). Most of the recent studies have shown that non-parametric machine learning approaches such as Artificial Neural Network (ANN), Support Vector Machine (SVM), and Random Forest (RF) have a great potential to classify heterogeneous land covers (Wessel et al 2018, Pacheco et al 2021, Sheykhmousa et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, they cannot comply with the user-specific requirements in space and time (Costa et al 2018). Several researchers found the Mediterranean countries, such as Portugal and Spain, with the lowest overall accuracy, below 70% out of all European countries mapped (Costa et al 2022, Liu et al 2021. National land cover mapping with higher accuracy and up-to-date and detailed data can use as a complementary product for larger mapping scales (Costa et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations